Studi Kualitatif Peran Kader dalam Pelaksanaan Layanan Stimulasi Deteksi dan Intervensi Dini Tumbuh Kembang (SDIDTK) - Ratnaningsih, Ester; Febriati, Listia Dwi; Sugathot, Aan Ika (Jurnal Kesehatan, 2024)
The SDIDTK program is a comprehensive and quality program for child growth and development through early stimulation, detection and intervention of developmental deviations in the first five years of life. Cadres have a very crucial role in the implementation of Integrated Healthcare Post (Posyandu) and act as one of the keys to success in SDIDTK.This study aims to analyze the roles of cadres in the implementation of SDIDTK services in the work area of Banguntapan 2 Community Health Center of Bantul. Qualitative study design by conducting in-depth interviews with related parties. The respondents were assigned into three groups including 4 cadres in 4 villages in the work area of Banguntapan 2 CHC (Community Health Center), 2 mothers of under-five children and 1 SDIDTK coordinator in Banguntapan 2 CHC. It was revealed that SDIDTK service at Banguntapan 2 CHC was implemented every 2 months by CHC staffs. As an implementer in SDIDTK services, cadres had the role in monitoring growth and finding deviations in child development; as a communicator, they had the role in providing information to mothers about the implementation of SDIDTK in Posyandu; as a motivator, they had the role in evaluating mothers who had not implemented SDIDTK; and as an organizer, they had the role in organizing SDIDTK services in Posyandu. SDIDTK services had not been implemented optimally due to inhibiting factor, that is not all Posyandu cadres had received SDIDTK training. In addition, the supporting facilities for SDIDTK services at Posyandu were considered inadequate. Cadres had several roles in SDIDTK services at posyandu involving the roles as implementer, communicator, motivator, and organizer. Relative parties are expected to facilitate Posyandu cadres in improving SDIDTK service competency by providing SDIDTK training to all cadres, as well as giving awards to active and outstanding cadres.